2016
DOI: 10.1016/j.ijsu.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of active surveillance of small renal masses

Abstract: Most SRMs are benign tumors or RCCs with a relatively indolent clinical behaviour. AS can be offered to patients with SRMs and decreased life expectancy. Prospective series of AS of histologically confirmed RCCs are needed to confirm the long term safety of this conservative approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 54 publications
(61 reference statements)
1
7
0
1
Order By: Relevance
“…We included 20 systematic reviews from 7098 references identified from our database search (fig 1). 7 8 9 28 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 These 20 systematic reviews included 240 primary studies and 627 073 patients. Fifteen systematic reviews provided data to quantify the prevalence of detecting incidentalomas7 8 9 28 30 31 32 33 34 35 36 37 38 39 45 (table 1), whereas 18 provided data to quantify the outcomes of incidentalomas7 8 9 28 30 31 32 33 34 35 38 39 40 41 42 43 44 45 (table 2) (13 provided both).…”
Section: Resultsmentioning
confidence: 99%
“…We included 20 systematic reviews from 7098 references identified from our database search (fig 1). 7 8 9 28 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 These 20 systematic reviews included 240 primary studies and 627 073 patients. Fifteen systematic reviews provided data to quantify the prevalence of detecting incidentalomas7 8 9 28 30 31 32 33 34 35 36 37 38 39 45 (table 1), whereas 18 provided data to quantify the outcomes of incidentalomas7 8 9 28 30 31 32 33 34 35 38 39 40 41 42 43 44 45 (table 2) (13 provided both).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for the effectiveness of AS for DCIS, RCC or CLL is accumulating, [ 5 9 ] yet this scoping review found a paucity of research on patient or provider views and experiences of PE in decision-making for AS compared with prostate cancer for which AS is a standard option. [ 3 , 4 ] Among patients with DCIS, there was no difference in concern or treatment preferences if the condition was referred to as “abnormal cells” or “cancer”.…”
Section: Discussionmentioning
confidence: 99%
“…AS avoids or postpones definitive cancer treatment until there is evidence from periodic observation or testing that a patient is at risk of or has disease progression [ 2 ]. AS is considered a management option for patients with prostate cancer [ 3 , 4 ], and research is accumulating to establish the clinical effectiveness of AS for renal cell carcinoma (RCC) [ 5 , 6 ], ductal carcinoma in situ (DCIS) of the breast [ 7 ], follicular lymphoma [ 8 ] and chronic lymphocytic leukemia (CLL) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Post-treatment care and contrast-enhanced imaging examinations are performed at intervals of 1, 6 and 12 months after the initial procedure and once each year thereafter [ 6 , 17 ]. Some elderly patients with small renal tumors are actively monitored without any surgical or interventional treatment [ 18 , 19 ]. They are often urologically asymptomatic and other diseases are much more serious and important for their life expectancy.…”
Section: Discussionmentioning
confidence: 99%